2015
DOI: 10.1183/13993003.01567-2015
|View full text |Cite
|
Sign up to set email alerts
|

Bronchiectasis: how to be an orphan with many parents?

Abstract: @ERSpublications Bronchiectasis, an orphan disease in the spotlight: more common than previously thought yet lots still to discover http://ow.ly/Ut1eT When René Laennec first described bronchiectatic lesions, he wrote: "Je me contenterai donc de donner deux exemples propres à faire connaître plus amplement l'altération organique assez rare dont il s'agit" [1]. Loosely translated, it shows us that during his discovery he had the conviction that bronchiectatic lesions were a rather rare phenomenon. However, at t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
0
2

Year Published

2016
2016
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(26 citation statements)
references
References 27 publications
0
24
0
2
Order By: Relevance
“…based on prior exacerbation history), patient phenotyping or endotyping is beyond the scope of such a document. Likewise, the guideline cannot address treatable comorbidities, environmental, lifestyle and psychological factors, which can also impact on patient outcomes [2,[29][30][31][32]. Providing holistic care for patients with bronchiectasis requires taking these factors into consideration as well.…”
Section: Chronic Pseudomonas Infectionmentioning
confidence: 99%
“…based on prior exacerbation history), patient phenotyping or endotyping is beyond the scope of such a document. Likewise, the guideline cannot address treatable comorbidities, environmental, lifestyle and psychological factors, which can also impact on patient outcomes [2,[29][30][31][32]. Providing holistic care for patients with bronchiectasis requires taking these factors into consideration as well.…”
Section: Chronic Pseudomonas Infectionmentioning
confidence: 99%
“…Bronchiectasis is a lung condition associated with chronic cough and sputum production that is rapidly increasing in prevalence in Europe [2]. It is a neglected disease, but recent initiatives including the European Bronchiectasis Registry and research network (EMBARC) and the European Union supported European Reference Network for Rare Pulmonary Diseases (ERN-LUNG) are beginning to raise the diseases profile and stimulate new research [3,4]. Patient involvement has been, and remains, central to these projects including the recently published European bronchiectasis guidelines which were developed with patients as members of the panel [5].…”
Section: Introductionmentioning
confidence: 99%
“…This presumption, however, has been challenged recently and some experts believe rightly that bronchiectasis is not an orphan disease. [ 1 ] Recent data from Western countries estimate a much higher prevalence and incidence of bronchiectasis than the threshold of 5/10,000 population for the definition of an orphan disease as defined by the European Union. [ 1 ] A study from the United Kingdom showed an increase in the incidence from 21.2/100,000 person-years in 2004 to 35.2/100,000 person-years in 2013 in women and from 18.2/100,000 person-years in 2004 to 26.9/100,000 person-years in 2013 in men.…”
Section: Introductionmentioning
confidence: 99%
“…[ 1 ] Recent data from Western countries estimate a much higher prevalence and incidence of bronchiectasis than the threshold of 5/10,000 population for the definition of an orphan disease as defined by the European Union. [ 1 ] A study from the United Kingdom showed an increase in the incidence from 21.2/100,000 person-years in 2004 to 35.2/100,000 person-years in 2013 in women and from 18.2/100,000 person-years in 2004 to 26.9/100,000 person-years in 2013 in men. [ 2 ] A recent population-based estimation of bronchiectasis prevalence in Germany estimated an overall prevalence rate of 67/100,000 in 2013 and a higher prevalence in elderly men (75–84 years) of 228/100,000.…”
Section: Introductionmentioning
confidence: 99%